Development and validation of an index to predict personal prescription drug importation by adults in the United States. Issue 1 (17th February 2015) - Zullo, Andrew R; Dore, David D; Galárraga, Omar
Abstract: Objective: Personal prescription drug importation (PPDI) is prevalent in the USA because of the high cost of US medicines and lower cost of foreign equivalents. The practice carries the risk of exposure to counterfeit, adulterated and substandard medicines. No known tools are available for predicting person-level PPDI risk. The objective of this study was to develop and validate a predictive PPDI index for policymakers, researchers and clinicians. Methods: Using 2011 and 2012 National Health Interview Survey data as the development and validation cohorts respectively, we identified predictors, built multivariable logistic regression models and validated the index by comparing predicted risk of PPDI in the development cohort with the observed risk in the validation cohort. We assessed calibration using the Hosmer–Lemeshow goodness-of-fit test and discrimination with C -statistics. The outcome measure was survey-reported PPDI (1 = yes; 0 = no). Key findings: In the development cohort, prevalence of PPDI in respondents with 0–2, 3, 4, 5–6 or ≥7 risk factors were 0.32%, 0.57%, 1.09%, 2.95% and 13.67% ( C -statistic = 0.78), and in the validation cohort, were 0.32%, 0.54%, 0.95%, 2.89% and 10.80% ( C -statistic = 0.76). The Hosmer–Lemeshow test indicated the absence of a gross lack of fit ( P = 0.58) in the validation cohort. Conclusion: This predictive index accurately stratifies US adults into groups at differential risk of PPDI and may provide value to those who are responsible for health policy and regulation of pharmaceutical importation.